2010
DOI: 10.1159/000314367
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adverse Drug Reactions to Cephalosporins in Penicillin Allergy Patients with Positive Penicillin Skin Test

Abstract: Background: Cephalosporin administration in patients with a history of penicillin allergy is controversial. Studies looking at the safety of cephalosporin in patients with a history of penicillin allergy lacked a control group, had a small number of patients, and/or lacked confirmation of penicillin allergy by penicillin skin testing. The purpose of this study was to determine whether patients with penicillin allergy were at increased risk of adverse drug reactions when administered cephalosporin. Methods: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 47 publications
(42 reference statements)
1
28
2
1
Order By: Relevance
“…In the current study, 0.7% (1 of 152 patients) had an adverse drug reaction to a cephalosporin in patients with a history of penicillin allergy and negative penicillin skin test compared to none in penicillin skin test-positive patients with a history of penicillin allergy. The low rate of adverse drug reaction to a cephalosporin in patients with a history of penicillin allergy and a negative penicillin skin test is consistent with our recent study in adults that showed an adverse drug reaction rate of 0.7% when challenged with a cephalosporin in patients with a history of penicillin allergy and a negative penicillin skin test [8]. Our study is also consistent with the literature review by Kelkar and Li [17] who found an adverse drug reaction of 0.6% in patients challenged with a cephalosporin with a history of penicillin allergy and a negative penicillin skin test.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, 0.7% (1 of 152 patients) had an adverse drug reaction to a cephalosporin in patients with a history of penicillin allergy and negative penicillin skin test compared to none in penicillin skin test-positive patients with a history of penicillin allergy. The low rate of adverse drug reaction to a cephalosporin in patients with a history of penicillin allergy and a negative penicillin skin test is consistent with our recent study in adults that showed an adverse drug reaction rate of 0.7% when challenged with a cephalosporin in patients with a history of penicillin allergy and a negative penicillin skin test [8]. Our study is also consistent with the literature review by Kelkar and Li [17] who found an adverse drug reaction of 0.6% in patients challenged with a cephalosporin with a history of penicillin allergy and a negative penicillin skin test.…”
Section: Discussionsupporting
confidence: 90%
“…The lack of any adverse drug reaction to a cephalosporin in patients with a history of penicillin allergy and a positive penicillin skin test contrasts with our recent study in adults that showed a 6% adverse drug reaction rate to cephalosporins in patients with a history of penicillin allergy and positive penicillin skin test [8]. Moreover, Atanaskovic-Markovic et al [18], in a pediatric population, showed that patients with a history of penicillin allergy and a positive penicillin skin test were also more likely to be skin test positive to cephalexin (23.9%), cefaclor (23.8%), ceftriaxone (0.7%) and cefotaxime (0.3%).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…[65][66][67] Thus, patients allergic to amoxicillin with a non-type 1 (late or delayed, >72 hours) hypersensitivity reaction can safely be treated with cefdinir, cefuroxime, or cefpodoxime. [66][67][68] Patients with a history of a serious type 1 immediate or accelerated (anaphylactoid) reaction to amoxicillin can also safely be treated with cefdinir, cefuroxime, or cefpodoxime.…”
Section: Kas Profilementioning
confidence: 99%
“…[66][67][68] The susceptibility of S pneumoniae to cefdinir, cefpodoxime, and cefuroxime varies from 60% to 75%, [56][57][58][59] and the susceptibility of H influenzae to these agents varies from 85% to 100%. 56,58 In young children (<2 years) with a serious type 1 hypersensitivity to penicillin and moderate or more severe sinusitis, it may be prudent to use a combination of clindamycin (or linezolid) and cefixime to achieve the most comprehensive coverage against both resistant S pneumoniae and H influenzae.…”
Section: Kas Profilementioning
confidence: 99%